(untitled) (Confluenţe Bibliologice, 2026)
The article focuses on examining information and analyzing the sources, data, and evidence used in the collection development process of the Scientific Library of USARB. It also reviews research tools, collection assessment methods, the use of concrete information, and the technological changes that contribute to the advancement of library collections.